(untitled) (SP Swag: Sudur Paschim Wisdom of Academic Gentry Journal, 2025)
This study analyzes key factors influencing individual investors’ decision-making in the stock market and examines how changes in subgroup investment affect their choices. Using primary data, the research investigates factors such as investors’ product purchasing information, psychology, regulatory policies, subgroup index changes, and investment decisions. To achieve the objectives, tools like tables, percentages, modes, medians, and ordinal logistic regression were applied. Data from 193 respondents, collected via physical and online surveys mainly from Kathmandu Valley, indicate most investors are young (ages 21-40), male, married, and from Bagmati province. Findings show that investors’ financial goals and investment horizons influence their behavior; some focus on long-term capital appreciation while others prefer short-term gains or income. The study highlights major determinants of investment decisions and the effects of subgroup index changes on investor behavior. The research concludes that investors’ information about stock purchasing, psychological factors, regulatory policies, and economic conditions significantly affect investment decisions, which are also impacted by changes in subgroup index investments.